Future Generation Education on Augmented Reality - Kumar, K. Ganesh (International Journal of Computer Sciences and Engineering, 2025)
Educator says that the learning process should be all about creativity and interaction. While teachers do not necessarily need to recruit all students into subject, their goal is to get them interested in a subject. Augmented Reality technology has the potential to blend both real and virtual environment to create an enhanced learning experience. Besides compared to paper-based solutions and conventional mobile applications, AR book system with scaffolding models they developed could help students to learn, particularly those with low reading ability. Objective of this paper is to highlight the applications and opportunities of research on AR applications in education.